Study on the perception of the use of information and communication technologies in higher education - Torres, Ana Paula [UNESP]; Pimenta, Leny Andre [UNESP]; Miceli Kerbauy, Maria Teresa [UNESP] (Centro Univ La Salle-rj, 2017)
The purpose of this article is to deepen the discussion about the use of Information and Communication Technologies (ICT) in higher education. The theoretical research model included the collection of information on four variables: 1. Technology; 2. Learning process; 3. Teacher-Student Interaction; and 3. Demographic characteristics of the participants (gender, age group, schooling, teacher's exercise) to analyze the perception of students and teachers about the use of (ICT) in higher education. The adopted research instrument considered twenty questions and was applied to undergraduate students in Pedagogy; Masters and doctoral students and professors of the Post-Graduate Program in School Education of the College of Sciences and Literature - Unesp. Based on the obtained results it was evidenced that the Information and Communication Technologies as mediators of the teaching and learning process involve much more than the use, access and appropriation of technological and methodological innovations in the educational processes; involve the social construction of knowledge.
Keywords: Education; Information and communication technologies; Higher education